The Contribution of Spiritual Intelligence to The Self-Control and Respect Value of Adolescent Football Athletes - Rendi Chandra Rihadi; Yusup Hidayat; Dikdik Zafar Sidik (Universitas PGRI Palembang, 2022)
This study aims to determine the relationship between spiritual intelligence, self-control and respect values. The research method used in this study is the Causal research (Expost-Facto) method. In this study, the sampling technique used non-probability sampling, namely by purposive sampling. The sample in this study was 33 people. The results showed that there wasa significant contribution between spiritual intelligence and self-control with a correlation coefficient of 0.520** with a significance value of 0.002<0.05, there wasa significant contribution between spiritual intelligence with a respect value with a correlation coefficient of 0.461** with a significance value of 0.00 7<0.05, and there isa significant relationship between spiritual intelligence and self-control value Significance (Sig) of the respect variable is 0.049. Because of the value of Sig. 0.049 < probability of 0.05, also from the calculation of tcount of 2.0 52 above compared to ttable (db = 31) which is 2.034 significantly 5%, so tcount > ttable.